Early in vitro evidence indicates that deacetylated sialic acids modulate multi-drug resistance in colon and lung cancers via breast cancer resistance protein - Tuffour, Isaac; Amuzu, Setor; Bayoumi, Hala; Surtaj, Iram; Parrish, Colin; Willand-Charnley, Rachel (Frontiers in Oncology, 2023)
Cancers utilize sugar residues to engage in multidrug resistance. The underlying mechanism of action involving glycans, specifically sialic acid (Sia), is not well understood. ATP-binding cassette (ABC) transporter proteins, a key component in multidrug resistance (MDR) pathways utilized by cancers, contain Sias in their extracellular domains. Sia can contain a variety of functional groups alterations, including 9-O and 7,9- O-acetylation on the C6 hydroxylated tail. Modulating the expression of acetylated Sias in lung and colorectal cancer cells directly impacted the ability of cancer cells to either retain or efflux chemotherapeutics via Breast Cancer Resistance Protein (BCRP), a significant ABC transporter implicated in MDR. Via CRISPR-Cas-9 gene editing, acetylation was modulated by the removal of Sialate O-Acetyltransferase, also known as CAS1 Domain-containing protein (CASD1), and Sialate O-Acetyl esterase (SIAE) genes. Using a variety of approaches including western blot, immunofluorescence, mRNA expression, and drug sensitivity analysis, we observed that CASD1 knockout cells that lack acetylated Sia expressed high levels of BCRP, resulting in an increased BCRP efflux activity, reduced sensitivity to the anticancer drug, Mitoxantrone, and demonstrated high proliferation relative to control cells. These observations correlated with increased levels of cell survival proteins, BcL-2 and PARP1. Further studies implicated the lysosomal pathway as the route responsible for the observed variation in BCRP levels among the cell variants. Microarray data analysis of clinical samples revealed higher CASD1 expression as a favorable marker of survival in lung adenocarcinoma. Collectively, our findings indicate that deacetylated Sia are utilized by colon and lung cancers to engage in MDR via overexpression and efflux action of BCRP.